Determinants of green bond premium in the ASEAN market amidst the COVID-19 pandemic - Oktavio, Laurent; Riyanti, Ririen Setiati (Jurnal Keuangan dan Perbankan, 2021)
Green bonds as a means of financing instrument for sustainable projects have caught the eyes of investors in recent years. With the growth of the global green bond market exceeding 50% in 2019 (CBI, 2019), green bonds serve as a promising financial instrument for organizations and a promising financial asset for investors. Previous studies have conflicting results in identifying the premium investors pay for investing in green bonds where both a positive and negative premium was observed. This study aims to examine the premium of green bonds issued in Southeast Asia before and during the COVID-19 pandemic from March 2016 to April 2021 by using a two-step regression model. In the first step, by employing a fixed-effect model to 42 green bonds, the results of this study suggest a positive green bond premium before the COVID-19 pandemic and a negative green bond premium during the pandemic. Additionally, this study conducts cross-section regressions to investigate the determinants of green bond premium. The results imply that rating, currency, issue amount, and time to maturity significantly affect the green bond premium.JEL: C23, G12, G14, G20, Q56